1993
DOI: 10.1172/jci116386
|View full text |Cite
|
Sign up to set email alerts
|

Dietary induced subclinical vitamin K deficiency in normal human subjects.

Abstract: A subclinical vitamin K deficiency was induced in 32 healthy subjects (four groups of eight males and females) aged 20-40 and 60-80 yr residing in the Metabolic Research Unit of the Human Nutrition Research Center on Aging at Tufts University. Volunteers were initially fed (4 d) a baseline-period diet containing the recommended daily allowance for vitamin K which is equivalent to 80 ;tg/d of phylloquinone (vitamin K1).During the baseline period various parameters of vitamin K nutritional status were monitored.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
72
0
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(81 citation statements)
references
References 24 publications
7
72
0
2
Order By: Relevance
“…The high phylloquinone concentrations in the cohort of Chinese women from Shenyang where osteoporotic fractures are rare (Yan et al, 1999), is compatible with the association of low circulating phylloquinone with a high incidence of osteoporotic fracture in Britain and North America (Hart et al, 1985;Bitensky et al, 1988;Roberts et al, 1996;Booth et al, 2000). Plasma phylloquinone concentration is readily affected by dietary intake and rapidly raises blood concentrations, which then fall within a few hours (Suttie et al, 1988;Ferland et al, 1993;Sokoll et al, 1997;Booth et al, 1999). Plasma phylloquinone also correlates with vitamin K intake in population studies (Booth et al, 1995.…”
Section: Ethnic Differences In Osteocalcin C-carboxylation Sr Beavan mentioning
confidence: 79%
“…The high phylloquinone concentrations in the cohort of Chinese women from Shenyang where osteoporotic fractures are rare (Yan et al, 1999), is compatible with the association of low circulating phylloquinone with a high incidence of osteoporotic fracture in Britain and North America (Hart et al, 1985;Bitensky et al, 1988;Roberts et al, 1996;Booth et al, 2000). Plasma phylloquinone concentration is readily affected by dietary intake and rapidly raises blood concentrations, which then fall within a few hours (Suttie et al, 1988;Ferland et al, 1993;Sokoll et al, 1997;Booth et al, 1999). Plasma phylloquinone also correlates with vitamin K intake in population studies (Booth et al, 1995.…”
Section: Ethnic Differences In Osteocalcin C-carboxylation Sr Beavan mentioning
confidence: 79%
“…In some cases, higher levels of triglyceride-rich lipoproteins, with advancing age, can account for these higher concentrations. Ferland et al have shown a resistance among older adults in functional measures of vitamin K deficiency when placed on low vitamin K diets (262). This is probably due to greater vitamin K intake among older versus younger adults.…”
Section: Vitamin Kmentioning
confidence: 99%
“…Subclinical Vitamin K deficiency has been induced in healthy adults fed a diet providing about 10 micrograms of phyloquinone per day [3]. Vitamin K1 depletion dramatically and significantly decreased plasma vitamin K1 levels (P<0.0001) to values 13-18%.…”
Section: Editorialmentioning
confidence: 99%